The IMPLEMENTATION OF HEALTH EDUCATION FOR ELEMENTARY SCHOOL STUDENTS IN SAMARINDA CITY - Fransiska Novita; Maria Floriana Ping (JPMK : Jurnal Pengabdian Masyarakat Kasih Published by Unit Penelitian dan Pengabdian Kepada Masyarakat (UPPM) STIKES Dirgahayu Samarinda, 2026)
Introduction: Cognitive development can influence the behavior of elementary school students in adopting a healthy lifestyle. Objective: To provide health education to elementary school students in Samarinda City. Method: This activity was implemented in two sessions: the first session on nutritional status education and the second session on genital care education. Respondents consisted of 84 students in grades 4 and 5 at an elementary school in Samarinda City. Results and Conclusions: There was an increase in knowledge before and after the education, from insufficient knowledge (14%) to sufficient knowledge (59.%) and good knowledge (27%).